Proceedings of the International Graduate Research in Education Seminar i-GREduc 2024 - Faculty of Educational Studies (Faculty of Educational Studies, 2024)
The International Graduate Research in Education Seminar (i-GREduc) 2024, held on 23 November 2025 and organized by the Faculty of Educational Studies, Universiti Putra Malaysia, focused on the theme Future Ready Education: Innovating for Tomorrow’s Challenge.